2021
DOI: 10.1186/s12888-021-03593-5
|View full text |Cite
|
Sign up to set email alerts
|

Treating alcohol use disorder in the absence of specialized services – evaluation of the moving inpatient Treatment Camp approach in Uganda

Abstract: Background The gap between service need and service provision for alcohol-related disorders is highest in resource-poor countries. However, in some of these contexts, local initiatives have developed pragmatic interventions that can be carried out with limited specialized personnel. In an uncontrolled treatment study, we aimed to evaluate the feasibility, acceptability, safety, costs and potential effects of an innovative locally developed community-based program (the Treatment Camp) that is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Some unique service delivery mechanisms were mentioned in the literature, such as Uganda's mobile detoxification and rehabilitation unit [ 61 ]. Furthermore, there was a large variation in patients' durations of stay observed in the literature, with a duration of inpatient or residential treatment ranging from one week to several years [ 44 , 45 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some unique service delivery mechanisms were mentioned in the literature, such as Uganda's mobile detoxification and rehabilitation unit [ 61 ]. Furthermore, there was a large variation in patients' durations of stay observed in the literature, with a duration of inpatient or residential treatment ranging from one week to several years [ 44 , 45 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite challenges, it is important to celebrate the achievements of AOD use treatment and prevention efforts in several African countries. For example, there are innovative treatment programs in resource-poor areas, such as the treatment camp approach in Uganda [ 121 ]. However, not all of these programs have been rigorously evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment package included home delivery, adherence support, and side effect monitoring of low-dose neuroleptic medication (Odenwald et al, 2012). The other study reported on a mobile inpatient detoxification program for alcoholdependent adults, which moved together with counselors and medical staff every 7 days to a different community in Northern Uganda (Ertl et al, 2021). The detoxification included medication delivery (benzodiazepines, neuroleptic medication, antidepressants, anticonvulsants) and monitoring and was complemented by psychotherapeutic content.…”
Section: Psychopharmacological Interventionsmentioning
confidence: 99%